Релігійний туризм в Греції - Овчарик Єлизавета Михайлівна (My University, 2021)
The master's thesis contains analysis of the state of development of religious tourism in Ukraine and identifies the main problems and benefits for the organization of religious tours. The concept of religious tourism, its purpose, types and forms are defined. The advantages of tourism in Greece are analyzed, the main sacred monuments of the country that are of significant religious and historical value are identified. Based on a study of the peculiarities of the organization of religious tours and analysis of proposals in the tourist market of Ukraine, a new tourist route to the shrines of Greece was proposed by author. The sightseeing tour includes visits to the shrines of Thessaloniki and the complex of monasteries of Meteora, acquaintance with the religion, history and culture of Greece.

У магістерській роботі проаналізований стан розвитку релігійного туризму в Україні, виявлені основні проблеми та переваги для організації релігійних турів. Визначено поняття релігійного туризму, його мета, види та форми. Проаналізовані переваги туризму в Греції, визначені основні сакральні пам’ятки країни, що становлять значну релігійну та історичну цінність. На основі дослідження особливостей організацій релігійних турів та аналізу пропозицій на туристичному ринку України запропонований новий туристичний продукт до святинь Греції. Туристичний продукт екскурсійно-пізнавальної спрямованості передбачає відвідування святинь міста Салоніки та комплексу монастирів Метеора, знайомство з релігією, історією та культурою Греції.